ABO Blood Group: Risk factors for malaria in hypoendemic areas? - Lambok Siahaan (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACT Background: Malaria is a parasitic infectious disease that is transmitted by vectors. This disease can cause death, especially in babies, toddlers and pregnant women. This research was conducted to prove whether there was a relationship between blood group and the occurrence of malaria infection. Methods: The sample was people who permanently reside in the research area and have risk factors for exposure to malaria. Diagnosis was made through microscopic examination. Blood type was tested using the slide method. Results: The most common cause of malaria was Plasmodium vivax. There were no significant differences between etiology, clinical symptoms, hemoglobin levels and parasite density with ABO blood group. This study found no significant differences between ABO and malaria blood types. Conclusion: ABO blood type cannot be used as a risk factor in hypoendemic areas which have the majority of vivax malaria sufferers.